Pyelonephritis in Pregnancy: Relationship of Fever and Maternal Morbidity - DeYoung, Tracey H.; Whittington, Julie R.; Ennen, Christopher S.; Poole, Aaron T. (American Journal of Perinatology Reports, 2019)
Objective To evaluate the relationship between maternal fever at the time of hospital admission and subsequent maternal morbidity in pregnant patients with pyelonephritis.Study Design In this retrospective cohort study, inpatient records were reviewed for all obstetric patients discharged from a single tertiary care hospital between June 1, 2011, and May 30, 2017, with the diagnosis of pyelonephritis. Patients were stratified into two groups, those with and without fever at the time of admission. Descriptive statistics were utilized to evaluate the association of fever at the time of presentation with subsequent morbidity. Using admission vital signs, maternal early warning criteria (MEWC) were applied and odds ratios calculated to predict intensive care unit (ICU) admission.Results A total of 110 patients were admitted with pyelonephritis in pregnancy; 24 patients were febrile and 86 patients were afebrile on admission. There was no difference in rates of maternal ICU admission between both groups. Positive MEWC was predictive of ICU admission with an adjusted odds ratio of 16.54 (95% confidence interval: 1.29–212.5; p = 0.03).Conclusion Afebrile pregnant patients with pyelonephritis remain at risk of significant maternal morbidity. Application of the MEWC on admission identifies patients at higher risk of ICU admission.
Keywords: pyelonephritis; pregnancy; fever; morbidity; acute respiratory distress syndrome; ARDS; MEWC; maternal early warning criteria